PENGARUH TEKNIK ROLE PLAYING TERHADAP KESTABILAN EMOSI PADA SISWA KELAS VIII SMP - Nidaan Khofia M; Ni Ketut Alit Suarti; Lalu Jaswandi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT Based on the results of preliminary observations, eighth grade students at SMP Negeri 4 Kuripan showed various academic problems related to emotional stability, such as feeling easily embarrassed, being moody, experiencing mood swings, and having difficulty controlling their emotions. These conditions affect students’ learning concentration, social interaction, and potential academic achievement. This study aims to determine the effect of the role playing technique on the emotional stability of eighth grade students at SMP Negeri 4 Kuripan in the 2024/2025 academic year. This research employed a quantitative approach with a one group pre test post test design. The research subjects were students who had low levels of emotional stability based on the results of the initial measurement. The data collection technique used a questionnaire as the main instrument, supported by observation, interviews, and documentation. The obtained data were then analyzed using the t test formula to determine the difference in conditions before and after the treatment. The results of the analysis showed that the t value was 6.487, which was greater than the t table value of 1.943 at the 5 percent significance level, indicating an increase in students’ emotional stability after being given the treatment in the form of the role playing technique. These findings indicate that the implementation of the role playing technique in group guidance services is effective in helping students understand and manage their emotions more positively, thereby supporting the learning process and students’ adjustment in the school environment. ABSTRAK Berdasarkan hasil observasi awal, siswa kelas VIII di SMP Negeri 4 Kuripan menunjukkan berbagai masalah akademik yang berkaitan dengan kestabilan emosi, seperti mudah merasa malu, murung, mengalami perubahan suasana hati, serta kesulitan mengendalikan emosi. Kondisi tersebut berdampak pada konsentrasi belajar, interaksi sosial, dan potensi pencapaian akademik siswa. Penelitian ini bertujuan untuk mengetahui pengaruh teknik role playing terhadap kestabilan emosi siswa kelas VIII di SMP Negeri 4 Kuripan Tahun Pelajaran 2024/2025. Penelitian ini menggunakan pendekatan kuantitatif dengan desain one group pre-test post-test. Subjek penelitian adalah siswa yang memiliki tingkat kestabilan emosi rendah berdasarkan hasil pengukuran awal. Teknik pengumpulan data menggunakan angket sebagai instrumen utama yang didukung oleh observasi, wawancara, dan dokumentasi. Data yang diperoleh kemudian dianalisis menggunakan rumus t-test untuk mengetahui perbedaan kondisi sebelum dan sesudah perlakuan. Hasil analisis menunjukkan bahwa nilai t-hitung sebesar 6,487 lebih besar daripada t-tabel sebesar 1,943 pada taraf signifikansi 5%, yang menunjukkan adanya peningkatan kestabilan emosi siswa setelah diberikan perlakuan berupa teknik role playing. Temuan ini menunjukkan bahwa penerapan teknik role playing dalam layanan bimbingan kelompok efektif membantu siswa dalam memahami dan mengelola emosi secara lebih positif sehingga dapat mendukung proses belajar dan penyesuaian diri di lingkungan sekolah.